In Silico Design, Synthesis and Evaluation of Hydroxyxanthone Derivatives as Potential Anti-diabetic Agents Targeting α-glucosidase - Saikia, Riya; Das, Aparoop; Pathak, Kalyani; Gogoi, Neelutpal; Paul, Tirna; Sahariah, Jon J.; Sarma, Himangshu (Current Enzyme Inhibition, 2022)
Background: Glucosidase is a catalytic enzyme that catalyzes, specifically hydrolyses, the carbohydrates to free glucose units in blood in the last step of carbohydrate metabolism. So far, many compounds with α-glucosidase inhibitory activity, for example, acarbose, voglibose etc., have been accounted and commercialized for diabetes therapy. However, xanthones are recognized as efficient glucosidase inhibitors because of their planar structure, and have opened the door for the researchers to utilize the same for designing and developing potent and novel hybrid xanthones for anti-diabetic therapy. Objectives: The current study aimed to determine and evaluate the anti-diabetic potential of different synthetic hydroxylxanthone derivatives using Nicotinamide and Streptozotocin (60mg/kg i.p.) induced diabetic rats. Methods: The partially purified synthetic hydroxyxanthone derivatives, namely A1, A2, A3, A4, and A5, were administered to diabetic rats at a dose of 150mg/kg per oral(p.o.), and the effect of the fraction on blood glucose level was studied for up to 21 days. Further, the synthetic compounds were subjected to spectral analysis for their characterization. Results: The in silico molecular docking results indicated that compound A3 has shown the best binding energy score. Also, the in vivo anti-diabetic potential of the synthetic hydroxyxanthone derivatives has revealed the compounds A3 and A2 to be significantly effective in controlling the blood glucose level when compared to the standard drug miglitol. In addition, compounds A3 and A2 were found to be effective in restoring the enzymes of the liver and lipid profile in Streptozotocin-induced Wistar rat models. Conclusion: With an objective to investigate the compounds for predicting biological activity, it was found that the hydroxyxanthone possesses a safety margin for toxicity and acts as a lead toward the development of potential α-glucosidase inhibitors. These compounds show an excellent correlation between docking results, synthetic data and in vivo anti-diabetic activity. However, further modifications can be done to enhance the potency and binding affinity profile, and minimize toxicity.
Keywords: hydroxyxanthone